2018
DOI: 10.1186/s40623-018-0795-7
|View full text |Cite
|
Sign up to set email alerts
|

Detection of water vapor time variations associated with heavy rain in northern Italy by geodetic and low-cost GNSS receivers

Abstract: GNSS atmospheric water vapor monitoringis not yet routinely performed in Italy, particularly at the regional scale. However, in order to support the activities of regional environmental protection agencies, there is a widespread need to improve forecasting of heavy rainfall events. Localized convective rain forecasts are often misplaced in space and/ or time, causing inefficiencies in risk mitigation activities. Water vapor information can be used to improve these forecasts. In collaboration with the environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 25 publications
1
35
0
1
Order By: Relevance
“…The development is now carried out mostly by GReD srl, with the contributions of users from several institutions, at international level. goGPS has applications in navigation (Realini et al, 2012), but also in other fields such as building monitoring (Caldera et al, 2016) and troposphere estimation (Barindelli et al, 2018).…”
Section: U-blox Gnss Data Processingmentioning
confidence: 99%
“…The development is now carried out mostly by GReD srl, with the contributions of users from several institutions, at international level. goGPS has applications in navigation (Realini et al, 2012), but also in other fields such as building monitoring (Caldera et al, 2016) and troposphere estimation (Barindelli et al, 2018).…”
Section: U-blox Gnss Data Processingmentioning
confidence: 99%
“…GNSS-derived tropospheric products are nowadays used in operational weather prediction applications and climate studies [5]. Some experiments based on GNSS atmospheric data have proved to be useful to study severe precipitation events [3,6,7]. A few assimilation experiments of GNSS tropospheric products into NWMs have proved to be beneficial to improve rainfall forecasts [1,8].…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al [11] reported that the weekly and monthly variations of total precipitable water vapor over the Arabian Sea and the Indian Ocean are well correlated with onset day of monsoon over the Indian sub-continent. Barindelli et al [12] reported a peak in the PWV values in response to a heavy precipitation event, followed by a steep decrease (5-10 mm in about 1 h) in the observed PWV values as the rain clouds moved past the station using data from a temperate station (of Italy). Shi et al [13] presented some severe rainfall cases and a series of moderate rainfall cases to indicate the feasibility of GPS-PWV values for rainfall monitoring using data from the sub-tropical stations (of China).…”
Section: Introductionmentioning
confidence: 99%